Ferrite, martensite and supercritical iron: A coherent elastochemical theory of stress-induced carbon ordering in steel. (1st October 2018) - Maugis, P.
Abstract: A mean-field model based on the elasticity theory of point defects has been developed to investigate the role of uniform stress fields on the long-range ordering of carbon atoms in bct-iron. From an analysis of the thermodynamic equilibria, composition – temperature – stress state diagrams are derived. We demonstrate that ferrite, martensite and supercritical iron are various instances of the same bct-iron phase region. A coherent mapping of the phase transitions is drawn, identifying (i) continuous transitions such as ferrite ordering, martensite enhanced ordering and ferrite – martensite transformation, and (ii) discontinuous transitions such as temperature-induced martensite and stress-induced martensite. Our analysis is supported by rigid-lattice Monte Carlo simulations. Recently published experimental results on highly-drawn perlitic wires are re-interpreted in terms of supercritical iron, rather than strain-induced martensite. Novel low-temperature thermomechanical treatments of supersaturated ferrite are suggested, for improved nanostructure design of martensitic steels. Graphical abstract: Image 1